ANALISIS PENGARUH PEMBELIAN DAN PENJUALAN KEPADA PIHAK YANG BERELASI DAN TIDAK BERELASI TERHADAP LABA BERSIH PADA INDUSTRI OTOMOTIF DAN KOMPONENNYA - Indah Rini Handayani (Universitas Mercu Buana, 2014)
Abstract: This research is performed to test the influence of independent variables Purchase from related parties and third parties, Sales to related parties and third parties individually to earning after tax and knowing the most dominant independent variables towards earning after tax. Sampling 8 automotive companies listed on the Indonesia Stock Exchange from population 12 automotive company. Sampling technique used was purposive sampling. Data consisted of the cross section is 8 automotive and the time series 5 year period, amounting 40 data. Analysis of thedata used is a panel data regression. Hausman test performed using a Random Effects Model or Fixed Effects Model, having obtained the data processing model testing tstatistic. Based on the results of research, Purchase from Related Parties and Sales to third parties individually not significantly effect to earning after tax, Purchase from third Parties and Sales to Related parties individually significant effect to earningafter tax.Keywords: Purchase from related parties, Purchase from third parties, Sales to related arties, Sales to third parties, Earning after tax